State of the art of pricing policy in air transportation: network carriers vs. low-cost airlines - Wehner, Christian (2019)
The modern air transport industry is highly competitive. To survive in the market, the implementation of a successful marketing strategy is fundamental. In particular, an effective pricing policy has become crucial for airlines to remain profitable. Correspondingly, the different types of airline in the market have also established very distinct pricing policies. The present study is based on a literature review and presents the state of the art of pricing policy in air transportation. The aim is to compare and discuss the pricing strategies of network carriers and low-cost airlines. Special attention is paid to Revenue Management, which is a very important management tool used by airlines to take advantage of the differences in willingness to pay of passengers. The pricing policy, however, depends on the overall business strategy of the airline. Results show many differences, resulting from the fact that these two types of airline are characterized by very different fundamental business models and, correspondingly, also target groups. Since network carriers and also low-cost airlines have adjusted their pricing strategies lately, these recent developments will be discussed as well. This paper adds to the knowledge of this topic because it presents the most up-to-date and complete study on pricing regarding network carriers vs. low-cost airlines.